Bond yield spreads and short-term interest rate movements - Ismail, Abd Ghafar; Koris, Roshanim (Sekolah Pengurusan, Universiti Utara Malaysia, 2003)
The information content of the short end of the term structure depends on the stance of monetary policy. Based on the findings of several authors such as Simon (1990) and Hardouvelis (1988) the bond spreads can predict future short-term rate movements. Hence, we use monthly observations from 1997 to 2000 on inter-bank rate, treasury bill rates, government bond rates and corporate blond rates to better understand the relationship between the predictive power of the term structure and the stance of monetary policy.